Urinary incontinence and vaginal squeeze pressure two years post-cesarean delivery in primiparous women with previous gestational diabetes mellitus - Barbosa, Angélica Mércia Pascon [UNESP]; Dias, Adriano [UNESP]; Marini, Gabriela [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP]; Witkin, Steven Sol [UNESP]; Rudge, Marilza Vieira Cunha [UNESP] (Universidade de São Paulo (USP), Faculdade de Medicina, 2011)
OBJECTIVE: To assess the prevalence of urinary incontinence and associated vaginal squeeze pressure in primiparous women with and without previous gestational diabetes mellitus two years post-cesarean delivery.METHODS: Primiparous women who delivered by cesarean two years previously were interviewed about the delivery and the occurrence of incontinence. Incontinence was reported by the women and vaginal pressure evaluated by a Perina perineometer. Sixty-three women with gestational diabetes and 98 women without the disease were screened for incontinence and vaginal pressure. Multiple logistic regression models were used to evaluate the independent effects of gestational diabetes.RESULTS: The prevalence of gestational incontinence was higher among women with gestational diabetes during their pregnancies (50.8% vs. 31.6%) and two years after a cesarean (44.8% vs. 18.4%). Decreased vaginal pressure was also significantly higher among women with gestational diabetes (53.9% vs. 37.8%). Maternal weight gain and newborn weight were risk factors for decreased vaginal pressure. Maternal age, gestational incontinence and decreased vaginal pressure were risk factors for incontinence two years after a cesarean. In a multivariate logistic model, gestational diabetes was an independent risk factor for gestational incontinence.CONCLUSIONS: The prevalence of incontinence and decreased vaginal pressure two years post-cesarean were elevated among women with gestational diabetes compared to women who were normoglycemic during pregnancy. We confirmed an association between gestational diabetes mellitus and a subsequent decrease of vaginal pressure two years post-cesarean. These results may warrant more comprehensive prospective and translational studies.
Keywords: Cesarean delivery; Gestational diabetes mellitus; Vaginal squeeze pressure; Pregnant; Urinary incontinence